Multi-Objective Decision Making on Roadway Maintenance Engineering Considering ε-dominance. Issue 1 (March 2021) - Chen, Huilin; Wang, Jinmei; Cai, Wentao
Abstract: As an important part of state-owned assets, roads and other transportation infrastructure are an important foundation for the sustained and healthy development of the national economy. It is extremely important to increase the service life of roadways. Aiming at the highly restricted multi-objective optimization problem of roadway maintenance, this paper considers the three dimensions of construction schedule, cost and quality, and proposes an elitist evolutionary multi-objective optimization algorithm based on the concept of ϵ-dominance, called ϵ-multi-objective genetic algorithm variable (εv-MOGA) to solve roadway maintenance problems. Experimental results show that the algorithm can help decision makers choose the most suitable solution among a large number of feasible solutions.